New perspectives for investigating muscular perfusion response after dietary supplement intake: an exploratory, randomized, double-blind, placebo-controlled crossover trial in healthy young athletes using contrast-enhanced ultrasound (CEUS) - Bürkle, Franziska; Doll, Julian; Neide, Arndt; Gantz, Simone; Tsitlakidis, Stefanos; Fischer, Christian (Journal of the International Society of Sports Nutrition, 2022)
Background Various dietary supplements have been reported to enhance muscular perfusion in athletes practicing resistance training, especially through modulation of nitric oxide signaling. Objectives The aim of this study was therefore to investigate selected 'NO-boosting' supplements in a real-life setting i) to generate novel hypotheses and perfusion estimates for power calculation in view of a definitive trial and ii) to assess the feasibility of the study design with particular focus on the use of contrast-enhanced ultrasound (CEUS) for perfusion quantification. Methods Thirty young male athletes (24 +/- 4 years) regularly practicing resistance training were enrolled in this three-arm, placebo(PL)-controlled crossover trial with ingestion of two commercially available supplements: an amino acid combination (AA) (containing 3 g of L-arginine-hydrochloride and 8 g of L-citrulline-malate) and 300 mg of a specific green tea extract (GTE). After intake, CEUS examinations of the dominant biceps brachii muscle were performed under resting conditions and following standardized resistance exercising. Quantitative parameters of biceps perfusion (peak enhancement, PE; wash-in perfusion index, WiPI) and caliber were derived from corresponding CEUS video files. Additionally, subjective muscle pump was determined after exercise. Results For PE, WiPI, and biceps caliber, the standard deviation (SD) of the within-subject differences between PL, AA, and GTE was determined, thereby allowing future sample size calculations. No significant differences between PL, AA, and GTE were observed for biceps perfusion, caliber, or muscle pump. When comparing resting with post-exercise measurements, the increase in biceps perfusion significantly correlated with the caliber increase (PE: r = 0.266, p = 0.0113; WiPI: r = 0.269, p = 0.0105). Similarly, the biceps perfusion correlated with muscle pump in the post-exercise conditions (PE: r = 0.354, p = 0.0006; WiPI: r = 0.350, p = 0.0007). A high participant adherence was achieved, and the acquisition of good quality CEUS video files was feasible. No adverse events occurred. Conclusion Based on our novel examination protocol, CEUS seems to be feasible following higher-load resistance exercising and may be used as a new method for high-resolution perfusion quantification to investigate the effects of pre-exercise dietary supplementation on muscle perfusion and related muscle size dynamics.